The identity of Luperus metallicus Jacoby, 1894 (Coleoptera: Chrysomelidae: Galerucinae) - Bezděk, Jan (Zootaxa, 2024)
Luperus metallicus Jacoby, 1894, known from the Indonesian islands Bali, Sumbawa, Adonara and Timor, is redescribed and transferred to the genus Charaea Baly, 1878. Color photos of the habitus, body details, and drawings of the genitalia are presented.